Enhancement of chronic wound healing with maltodextrin/ascorbic acid gel: a clinical evaluation of distal limb wounds in horses - Ibrahim E. Helal; Hatim A. Al-Abbadi; Mohamed H. El-Daharawy; Mahmoud F. Ahmed (Journal of Animal Science and Technology, 2022)
Delayed healing associated with distal limb wounds is highly challenging in equine clinical practice. This study aimed to evaluate healing rates between chronic non-granulating wounds of horse distal limbs that were treated with maltodextrin/ascorbic acid gel alone or in combination with povidone-iodine 1% solution and those treated with povidone-iodine 1% only throughout the study period (35 days) in clinical settings. The study was conducted on 18 adult horses (3–15 years old). Based on the treatment regimen utilized, the horses were divided into three groups (n = 6), with each group having a similar mean wound area. The percentages of wound contraction, epithelialization, and overall wound healing were determined weekly for each wound. By the end of the study, the total wound healing percentage was significantly increased between the study groups (p < 0.05). The use of maltodextrin/ascorbic acid gel resulted in considerable wound contraction, rapid epithelialization, and complication-free wound healing. Based on the findings of this study, maltodextrin/ascorbic acid gel, independently or in combination with a 1% povidone-iodine solution, might be applied as a safe and effective wound healing promoting agent in horses with chronic non-granulating wounds.